2019
DOI: 10.1097/anc.0000000000000590
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Pathophysiology, Implications, and Treatment Options of Patent Ductus Arteriosus in the Neonatal Population

Abstract: Background: Patent ductus arteriosus (PDA) is the persistence of a fetal shunt between the pulmonary artery and the aorta. This structure normally closes in the first 3 days after birth; however, closure is delayed in up to 80% of infants born at 25 to 28 weeks of gestation. Persistent PDA results in pulmonary overcirculation and systemic hypoperfusion. Purpose: The purpose of this article is to review pathophysiology and treatment options for PDA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…Patent ductus arteriosus (PDA) is very common in preterm newborns and is inversely related to gestational age (weeks) (1). The incidence ranges from 60 to 80% for preterm infants born between 25 and 28 weeks and up to 90% for those born at 24 weeks (1,2).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patent ductus arteriosus (PDA) is very common in preterm newborns and is inversely related to gestational age (weeks) (1). The incidence ranges from 60 to 80% for preterm infants born between 25 and 28 weeks and up to 90% for those born at 24 weeks (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Patent ductus arteriosus (PDA) is very common in preterm newborns and is inversely related to gestational age (weeks) (1). The incidence ranges from 60 to 80% for preterm infants born between 25 and 28 weeks and up to 90% for those born at 24 weeks (1,2). PDA can result in a significant left-to-right shunting and has been associated with neonatal morbidities: bronchopulmonary dysplasia (BPD), intraventricular hemorrhage (IVH), acute renal failure, necrotizing enterocolitis (NEC), and retinopathy of prematurity (ROP) (1,(3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomized controlled trials (RCTs) exploring the effects of a prophylactic treatment of PDA found that the occurrence of both death and long-term neurodevelopmental outcomes was not reduced. However, observational studies demonstrated the association between PDA exposure duration and long-term morbidities (14,32,33). In addition, retrospective studies found a relationship between symptomatic hs-PDA and morbidity combined with mortality (3).…”
Section: Discussionmentioning
confidence: 99%
“…We did not change the policies during the study period, but we cannot exclude the fact that unknown differences in clinical practice or changes in the medical staff composition may have influenced the outcomes of the study. We used previously described criteria for the definition of hs-PDA (1,5,19,32,46). Even if other parameters could be useful to define the hemodynamic significance of a PDA, information regarding ECHO findings on pulmonary overflow and systemic steal was not collected.…”
Section: Discussionmentioning
confidence: 99%